2002
DOI: 10.1007/s00787-002-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The high prevalence of psychopathology in children with beta-thalassaemia reported in this study suggests that specific blood disorders have differential impact on affected children. This difference may be related to medical therapy advances in haemophilia so that haemophilic boys can lead an almost normal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Various authors have reported that up to 80% of children with thalassemia are likely to have psychological problems e.g. oppositional defiant disorder, anxiety disorders and depression ( 15 - 17 ). Although children with all types of blood disorders are exposed to similar stressors, those with thalassemia are unique in that they have to attend hospital regularly for blood transfusions ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported that up to 80% of children with thalassemia are likely to have psychological problems e.g. oppositional defiant disorder, anxiety disorders and depression ( 15 - 17 ). Although children with all types of blood disorders are exposed to similar stressors, those with thalassemia are unique in that they have to attend hospital regularly for blood transfusions ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a higher incidence of depressive and anxiety disorders and an impaired general functioning in β-TM patients (e.g., Sadowski et al, 2002). Clinical complications have also been found to impact negatively on children's self-concept (e.g., Yalçan et al, 2007).…”
mentioning
confidence: 99%
“…Research has shown relationship between thalassemia major and depression [26, 31]. Depression is confirmed as the most common psychiatric disorders in thalassemia patients in other studies [25, 28]. In the study of Marvasti et al's [32], the risk of depression was much higher in patients with thalassemia compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Other similar studies, in addition to the high prevalence of mental health, have reported high number of such disorders (such as anxiety and depression) requiring extensive follow-up [16, 26, 27]. Sadowski et al's study [28] shows that mental health problems in thalassemia patients (47.4%) is not only higher compared to healthy controls (26.3%), but also significantly higher than hemophilia patients (24.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation